Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 2—Description of two new species of Centrophorus and clarification of the status of Centrophorus lusitanicus Barbosa du Bocage & de Brito Capello, 1864 - White, William T.; Ebert, David A.; Naylor, Gavin J.p. (Zootaxa, 2017)
Centrophorus specimens with a distinctive long-based first dorsal fin (long-finned species) have previously been considered to be Centrophorus lusitanicus first described from Portugal. Critical examination of the original description and illustration reveal that C. lusitanicus should be considered a junior synonym of C. granulosus. However, the specimen considered to be the syntype of C. lusitanicus in the Natural History Museum in London is clearly a long-finned species and not conspecific with C. granulosus. A more detailed investigation revealed that this specimen should not be considered a syntype and was likely not originally collected off the coast of Portugal. Investigation of long-finned specimens of Centrophorus from the Indo-West Pacific and Eastern Atlantic revealed that two undescribed species exist and are herein formally described as C. lesliei and C. longipinnis. The two species are similar morphologically and belong to the long-snout Centrophorus group (e.g. C. isodon and C. harrissoni) but are clearly separable based on their very long first dorsal fins. The two species differ in relative length of the first dorsal fin and several other characters. They also differ genetically. Nonmetric multidimensional ordination based on morphometric data reveals both species level and ontogenetic differences. A short erratum is also provided for Part 1 of this revision of the Centrophorus due to two figure related errors which may cause some confusion.